2014
DOI: 10.1681/asn.2013070811
|View full text |Cite
|
Sign up to set email alerts
|

Tribbles Homolog 3 Attenuates Mammalian Target of Rapamycin Complex-2 Signaling and Inflammation in the Diabetic Kidney

Abstract: The endoplasmic reticulum (ER) stress response is activated in the diabetic kidney and functions to reduce ER protein accumulation and improve cellular function. We previously showed that tribbles homolog 3 (TRB3), an ER stress-associated protein, is upregulated in the diabetic kidney. Here, we investigated whether absence of TRB3 alters outcomes in diabetic nephropathy. Type 1 diabetes was induced in TRB3 wild-type and knockout ( 2/2 ) mice by low-dose streptozotocin, and the mice were followed for 12 weeks.D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 81 publications
0
31
0
Order By: Relevance
“…In addition, the high BMP2 doses required for human osteogenesis are associated with life-threatening inflammatory cervical swelling and adipogenic cyst-like bone formation [44,45]. Interestingly, Trb3 was revealed to inhibit expression of peroxisome proliferator-activated receptor g, a master regulator of adipogenesis, and serves as a negative regulator of proinflammatory cytokines [46][47][48]. The additional knowledge gained from this study may suggest a new complementary osteoinductive strategy using phenamil with noggin suppression to maximize osteogenic differentiation of ASC for bone regeneration and minimize potential adverse effects of current osteoinductive therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the high BMP2 doses required for human osteogenesis are associated with life-threatening inflammatory cervical swelling and adipogenic cyst-like bone formation [44,45]. Interestingly, Trb3 was revealed to inhibit expression of peroxisome proliferator-activated receptor g, a master regulator of adipogenesis, and serves as a negative regulator of proinflammatory cytokines [46][47][48]. The additional knowledge gained from this study may suggest a new complementary osteoinductive strategy using phenamil with noggin suppression to maximize osteogenic differentiation of ASC for bone regeneration and minimize potential adverse effects of current osteoinductive therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of mTORC1 by the specific inhibitor rapamycin protected renal cells from ER stress-induced apoptosis by enhancing autophagic activity [25]. Cunard and colleagues revealed that the expression of TRB3 was upregulated in the diabetic kidney, and that diabetic TRB3 knockout mice induced by streptozotocin developed higher levels of albuminuria and expressed increased levels of ER stress markers in the renal cortices and glomeruli [26]. They found that TRB3 suppressed mTORC1 activity by direct binding and enhanced autophagic activity.…”
Section: Autophagy Protects Renal Cells From Endoplasmic Reticulum Stmentioning
confidence: 99%
“…TRB3 is an ER stress-associated protein that is upregulated by free fatty acids and ROS through the PERK/CHOP UPR pathway [82]. We recently demonstrated that constitutive knockout of TRB3 worsens albuminuria, cytokine and chemokine expression in murine Type 1 diabetic kidney disease [107], supporting the protective effects of ER stress. Further studies in mice with transgenic and conditional knockouts of key ER stress-associated molecules will likely clarify the roles that these complex pathways play in the diabetic kidney.…”
Section: Er Stress In the Diabetic Rodent Kidneymentioning
confidence: 99%